Case report: Tunneling foreign body in the metatarsal bones of a dog - Wagoner, Hannah; Holland, Merrilee; Pansini, Katherine; McCarthy, Jess; Fiske, Kaitlin (Frontiers in Veterinary Science, 2022)
A 2-year-old male intact goldendoodle presented for intermittent lameness, persistent draining tracts, and radiographic identified boney lytic lesions involving the metatarsal region, which had persisted for approximately 8 months before presentation to our referral hospital. Radiographic and computed tomography (CT) images suggested a tubular structure encircling and tunneling through the right metatarsal bones. Exploratory surgery confirmed a circumferential rubber band foreign body, with lytic boney tunneling within the metatarsal bones. CT provided vital information to assist in the surgical planning for this patient with a chronic tunneling foreign body.